(untitled) (Journal of NELTA, 2013)
The article aims to investigate the impact of the reflective writing paper on non- English major learners’ learning autonomy in a Vietnamese context. The data was collected by means of questionnaire, competence tests and interviews. The participants did two reflective writing papers as an intervention during the research. The research results show the possibilities for teachers to modify their teaching methods through analysis of feedback from the subjects. The findings showed that most participants appreciated the role of the reflective writing paper and they were aware of the significance of learning autonomy in their study process. Journal of NELTA, Vol. 17 No. 1-2, December 2012, Page 104-128 DOI: http://dx.doi.org/10.3126/nelta.v17i1-2.8102